Pulmonary Support of Infants with Tracheotomies in a Regional Neonatal Intensive Care Unit - Attar, Mohammad A.; Pace, Rachael A.; Schumacher, Robert E. (American Journal of Perinatology, 2021)
Objective We evaluate patient characteristics, hospital course, and outcome by type discharge pulmonary support; mechanical ventilation (MV) or with tracheotomy masks (TM).Study Design We reviewed records of infants admitted to the neonatal intensive care unit (NICU) that underwent tracheotomy within their first year of life between 2006 and 2017. We evaluated patient characteristics, referral pattern, destination of discharge, and outcome by type of pulmonary support at discharge (MV vs. TM).Results Of the 168 patients, 63 (38%) were inborn, 91 (54%) transferred to our NICU, and 5 (3%) were readmitted after being home. Median gestational age at birth was 34 weeks. Twenty-three (14%) infants were transferred to hospitals closer to their homes (13 with MV and 10 with TM), and 125 (74%) were discharged home (75 on MV and 50 on TM). Twenty patients (12%) died in the regional center (RC). Among those discharged home from our RC, infants on MV were of lower birth weight and younger gestational age, had tracheostomies later in life, had longer duration between tracheostomy to discharge to home, and had longer total duration of hospitalization at the RC. In addition, infants in the MV group were more frequently dependent on MV at time of placement of tracheostomies, less frequently had congenital airway anomalies and more frequently having possibly acquired airway anomalies and more frequently having major congenital anomalies, more frequently treated with diuretics, inhaled medications and medications for pulmonary hypertension, and more frequently had gastrostomies for feeding compared with the TM group.Conclusion Patients with tracheostomies in the NICU and discharged from RC on MV or TM vary by patient characteristic, timing of tracheostomy placement, timing of discharge from RC, type of upper airway anomalies, duration of stay in the hospital, and complexity of medical condition at discharge.Key Points
Keywords: utilization; counseling; back transfer; home ventilation; regionalization